Stubborn Twig : Three Generations in the Life of a Japanese American Family - Kessler, Lauren (Book collections on Project MUSE., 2008)
The story of one Japanese American family's century-long struggle to adjust, endure and ultimately triumph in their new country, which starts with the arrival of Masuo Yasui in America in 1903.